Income Inequalities and their Social Determinants: an Analysis over Developed vs. Developing EU Member States - Ionut Jianu; Ioana Andrada Gavril; Silvia Elena Iacob; Andrei Hrebenciuc (Economic Computation and Economic Cybernetics Studies and Research, 2021)
This paper assesses the impact of certain social factors on income inequalities in the EU. We applied Panel Estimated Generalized Least Squares method on two clusters, developed vs developing countries. We concluded that the relationship between historical income inequality and its current dimensions is stronger in developing than in developed countries. We also found a higher capacity of social expenditure to reduce income inequality in developed countries, and a positive relationship between unemployment and income inequality in both clusters. Moreover, we identified a positive relationship between tertiary education attainment in developed EU countries, but a negative one in developing countries. Excessive income inequalities affect social and economic dimensions, this being a real issue which can only be addressed at governmental level, by effective and inclusive public policies, which shall be aligned with cultural, social, economic and fiscal features.
Keywords: C33; D63; O11; H55; 330; income; inequality; social determinants; development; panel